Analisis Pengembangan Produk Ikan Pindang Bandeng (Studi Kasus: UMKM Pindang Pelem) - Junianto; Lisa Gabriela; Denis Setia Prismayana; Firly Ryan Nouvaly (Jurnal Serambi Engineering, 2025)
The growing demand for salted milkfish products is driving innovation in product development to meet diverse consumer preferences. Product development strategies enable companies to remain competitive and attract more potential consumers. This research aims to analyze the development of brine milkfish products covering aspects such as raw materials, processing methods, product variations, packaging and marketing strategies at UMKM Pindang Pelem. The research adopts a survey method using purposive sampling techniques. The data are analyzed descriptively to provide a clear overview of the research findings. The results show that UMKM Pindang Pelem has developed its procurement of milkfish by expanding the selection of suppliers located near the production site. Processing methods have been improved by improving the cleanliness of raw milkfish, adding flavor enhancers and spices during brining, and extending the brining time. UMKM Pindang Pelem has shifted to using convenient packaging such as combinations of styrofoam plates, banana leaves and plastic wrap, as well as foam food containers and thin-walled boxes. Their marketing strategy has used WhatsApp platforms for promotion and market segment expansion.